The Role of Educational Management in Promoting Teacher Motivation and Job Satisfaction - Antonius, Aslin; Angraeni, Andi; Aulia, Rezki (Educia Journal, 2024)
This study explores the role of educational management in promoting teacher motivation and job satisfaction across primary and secondary schools. Using a quantitative research design, a stratified random sample of 300 teachers from 20 schools was surveyed using the Teacher Motivation Scale (TMS) and the Job Satisfaction Survey (JSS). Data analysis included descriptive statistics, Pearson correlation, multiple regression, and ANOVA to examine the relationships between management practices and teacher outcomes. The results revealed strong positive correlations between teacher motivation and job satisfaction, with both intrinsic and extrinsic motivation significantly influencing teacher engagement. Leadership styles, particularly transformational and instructional leadership, and administrative support were found to have a significant impact on teacher motivation and job satisfaction. Additionally, school type (primary vs. secondary) was identified as a significant factor influencing teacher motivation levels. The study's findings contribute to the literature by emphasizing the importance of a balanced approach to fostering both intrinsic and extrinsic motivation and the role of educational management in shaping a positive work environment. It also highlights the need for context-sensitive strategies to improve teacher outcomes, particularly by tailoring management practices to the specific needs of different school settings. The study's results provide valuable insights for policymakers and educational leaders seeking to enhance teacher satisfaction, retention, and overall educational quality.